2005
DOI: 10.1074/jbc.m411528200
|View full text |Cite
|
Sign up to set email alerts
|

The Pathway for the Production of Inositol Hexakisphosphate in Human Cells

Abstract: The yeast and Drosophila pathways leading to the production of inositol hexakisphosphate (InsP 6 ) have been elucidated recently. The in vivo pathway in humans has been assumed to be similar. Here we show that overexpression of Ins(1,3,4)P 3 5/6-kinase in human cell lines results in an increase of inositol tetrakisphosphate (InsP 4 ) isomers, inositol pentakisphosphate (InsP 5 ) and InsP 6 , whereas its depletion by RNA interference decreases the amounts of these inositol phosphates. Expression of Ins(1,3,4,6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 31 publications
2
69
1
Order By: Relevance
“…If IP3K were not participating in this metabolism, adriamycin likely would have little effect, but in this case adriamycin treatment abolishes the IP 5 response to Wnt3a. We propose that IP3K is the major enzyme to convert IP 3 to IP 4 as it was found in human (45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If IP3K were not participating in this metabolism, adriamycin likely would have little effect, but in this case adriamycin treatment abolishes the IP 5 response to Wnt3a. We propose that IP3K is the major enzyme to convert IP 3 to IP 4 as it was found in human (45).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of stimulation by Wnt3a, cells display little change in intracellular IP 3 or IP 5 levels when IPMK is suppressed by siRNA. Earlier studies report dramatic reductions in IP 5 accu- mulation in HEK293 and HeLa cells (45), as well as in Rat-1 cells (38), when IPMK expression was suppressed with siRNA. Unlike these earlier studies performed with serum-fed cells, our studies required that we eliminate serum to study the Wnt response, likely the basis for the differences in the effects observed in response to IPMK suppression.…”
Section: Resultsmentioning
confidence: 99%
“…This function may be superimposed upon a more general role of ITPK1 homologues in eukaryotes: contributing to the synthesis of higher inositol polyphosphates such as InsP 6 (33,37). However, the extent to which ITPK1 contributes to higher order inositol phosphate synthesis in mammals remains to be demonstrated in a range of conditions and cell types.…”
Section: )P 3 Does Not Stimulate Thismentioning
confidence: 99%
“…We did not use RNA interference to reduce expression of the InsP 5 kinase that synthesizes InsP 6 . This decision was based on previous experiments showing that "knockdown" of mammalian InsP 5 2-kinase expression induces gross changes in nuclear morphology (41), is pro-apoptotic (42), and generally toxic (43,44). Instead, we overexpressed MINPP, an InsP 6 phosphatase.…”
Section: The Effect Of Minpp Upon Insp 6 Levels and Nucleolinmentioning
confidence: 99%